THE INFLUENCE OF WORK DISCIPLINE, LEADERSHIP, AND MOTIVATION ON THE PERFORMANCE OF POLICE PERSONAL - Haeruddin, Haeruddin; Ibrahim, Ibrahim (Universitas Islam Lamongan, 2023)
This research explores the impact of work discipline, leadership, and motivation on the performance of North Pamona Police Sub-precinct members using a quantitative approach. A survey involving 45 members as samples was analyzed using statistics, including multiple linear regression. The results indicate that work discipline and leadership do not have a significant influence on performance, while motivation has a strong positive and significant impact. These findings are consistent with previous research that highlights motivation as an important factor for individual performance. Recommendations include improving motivation, evaluating leadership policies, regularly monitoring performance and motivation, as well as opportunities for further research.